Evaluasi Pembelajaran Matematika dalam Pemberdayaan Teknologi Digital Menggunakan Model Evaluasi CIPP di SMAN Pontianak - Egy Abdi; Indri Astuti; Afandi (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
This research was oriented to evaluate the mathematics learning in digital technology empowerment using the CIPP at SMAN 03 Pontianak. The researcher used indicators in the UNESCO ICT Competency Framework for Teachers (2018) to identify their existence and technical implementation in each learning agenda or CIPP evaluation sub-component. The research type applied was evaluative research with a qualitative approach. The evaluation output on aspects of the teacher's digital competence application in mathematics learning at research locations is on a low scale with an achievement percentage of 9.6%, with a percentage of <21% when assessed based on each component or sub-component of the CIPP evaluation model of digital competency application in learning mathematics even in some of the sub-components of needs analysis and identification of problems in the Context component and learning monitoring in the Process component did not identify elements of digital technology empowerment at all. Apart from being triggered by indicators of digital technology empowerment not specific to the Principal's academic supervision, the teacher contributed by not giving the special attention to the systematic implementation of the learning agenda along with elements of technology empowerment on it.